Pengaruh Konseling Behavior Therapy untuk Mengatasi Perilaku Terisolir pada Remaja - Arizona, Arizona (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2021)
This study aims to determine how the influence of behavior therapy counseling to overcome isolated behavior of junior high school students. In this study, researchers used qualitative research methods with a qualitative descriptive model. Subjects taken in this studyamounted to 7 students who came from class VIII. Data collection methods in this study using observation, interviews and documentation. The validity of the data used was data triangulation technique, in research the data used was source triangulation. The data analysis that the researchers used was inductive analysis with steps consisting of data reduction, data presentation, and the last, in the form of drawing conclusions. The results showed that behavior therapy counseling to overcome students' isolated behavior can be applied in junior high schools. This is evidenced by the results of research which show the isolated behavior of students before being given behavior therapy counseling services is in the low category. Meanwhile, after being provided with behavior therapy counseling services, it shows that 5 people are in the high category and the other 2 people are in the category that is in several indicator.